Resistance of black currant varieties against the common spider mite in the Forest conditions of Ukraine - Bakalova, A.; Tymoshchuk, T.; Gritsyuk, N.; Ivachenko, I. (Scientific Progress & Innovations, 2025)
In recent years, the common spider mite has damaged blackcurrants on a large scale in the Polissia of Ukraine. The study of the resistance of different varieties of black currant to the common spider mite led to the excellent conclusion that the use of resistant varieties in the cultivation of black currant can, first of all, reduce the amount of phytophagous density by two times and improve the quality of black currant berries. The collection of varietal research was carried out on the varieties Sofia Kyivska, Chernecha, Kharkiv Veleten, Titania, Ukraine, that is, on five varieties of Ukrainian selection. The standard variety was assigned to the black currant variety Ukrainka, which was compared to it to determine the greatest resistance of the studied currant varieties. On average, a bush of black currant has about 0.85 square meters of leaf area inhabited by a common spider mite of the Ukrainian standard variety according to the indicators of our research. Resistant varieties have a well-developed leaf structure. In unstable varieties, the leaf plate is thin and weak, so leaves damaged by a common spider mite dry up and fall off. Over the years of research, larvae of different ages were observed, already at the fourth age the larvae stop feeding and become an adult imago. In the collection of researched varieties, the common spider mite begins its biological development cycle from the first decade of June. The phenological calendar developed during the study showed that in the conditions of the Zhytomyr region, a common spider mite can have up to 12 generations. The combination of the phenological system of phytophagous development with the phenological development of black currant allows for a clear assessment of the predicted yield. According to estimates of economic efficiency, the yield ranges from 4.7 to 6.4 tons of berries per hectare. According to these indicators, the most resistant varieties of black currant, in relation to the general population of common spider mite, were determined, namely: Sofia Kyivska, Chernecha, the yield of which was from 5.8 to 6.4 t/ha, profit 55128 to 60134 UAH/ha with a profitability of 390 %.